Environmental impact assessment of China's waste import ban policies: An empirical analysis of waste plastics importation from Japan. (20th December 2021) - Sun, N.; Tabata, T.
Abstract: In January 2018, the Chinese government implemented a ban on importation of foreign waste, including waste plastics and other miscellaneous waste. Consequently, this ban has changed the global plastic recycling options. The aim of this study is to clarify the environmental impact of the ban between China and Japan, which is the largest exporter of plastic waste. The question of whether these policies are fundamentally helping to reduce the environmental burden has also been discussed from the viewpoints of China and Japan. Plastics have been classified into seven categories. Material flow analysis (MFA) and CO2 emissions derived in the MFA were applied to examine the material flow of waste plastics and compare CO2 emissions of virgin and recycled resins in Japan and China before, and after, the ban. A scope for the MFA including the recycling process of waste plastics, virgin resin production, and shipping between countries was proposed, and the transition of the material flow and CO2 emissions caused by China's waste import ban were evaluated. Material flow relevant to both Japan and China was set as the scope. Material flow crossing the scope, such as import of waste plastic into China from countries other than Japan, and export of waste plastic from Japan to countries other than China before the ban was excluded. The main finding of MFA is that the transition in material flow between 2016 and 2018 in China demonstrated high virgin resin imports and exports in 2016, and 28% of recycled waste plastics in China were derived from imported waste plastic. After the ban, the amount of waste plastic imports decreased by more than 99%, causing domestic virgin resin production to increase. Other findings include that CO2 emissions of the input of virgin materials increased by up to 10%, and the CO2 emissions derived from virgin resin production increased by up to 11% in 2018 compared those reported in 2016. With this transition, the CO2 emissions of 1 kg of raw materials in 2018 increased by 0.24 kg compared with 2016. In contrast, Japan's exports decreased, and domestic recycled plastic input increased. The CO2 emissions of 1 kg of raw materials in 2018 decreased by 0.07 kg compared with 2016. Highlights: Impact of China's waste plastic import ban was analyzed using MFA. China increased virgin resin at the expense of reduced imports of waste plastics. CO2 emissions from the production of 1 kg of virgin resin increased in China. Japan's recycling increased at the expense of reduced exports of waste plastics. CO2 emissions from the production of 1 kg of recycled resin increased in Japan.